Pola Integrasi Kurikulum Pesantren Salaf dalam Mengembangkan Potensi Keagamaan dan Karakter Kewirausahaan di Pondok Pesantren Sidogiri Banat 1 Pasuruan - Rumiati; Ahmad Nurul Kawakib; Parmujianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the curriculum integration pattern of traditional Islamic boarding schools in developing religious potential and entrepreneurial character at the Sidogiri Banat 1 Islamic Boarding School in Pasuruan. In the context of changing times that demand independence and applicable life skills, Islamic boarding schools are required not only to be centers of spiritual strengthening, but also as a place to form productive and innovative characters. This study is important because it is able to show that the tradition of classical Islamic knowledge can synergize with entrepreneurship education without losing the substance of Islamic values. The study used a descriptive qualitative approach with participatory observation techniques, in-depth interviews, and documentation. The results of the study showed that curriculum integration was carried out by combining the diniyah education system based on yellow books with structured entrepreneurship training. Business practice activities such as food production, management of student cooperatives, and household skills are combined with strengthening morals, worship, and positive behavioral habits in the Islamic boarding school environment. This integration pattern is not carried out formally, but is rooted in traditional values ​​that are strengthened by the culture of the Islamic boarding school itself. The implication of this integrative curriculum pattern is the formation of the character of students who not only understand religion, but are also independent, disciplined, responsible, and have an entrepreneurial mentality. Sidogiri Banat 1 Islamic Boarding School is an example that traditional Islamic boarding schools can become a center for sustainable religious and economic empowerment of students. This study recommends the replication of a similar integration model in other traditional Islamic boarding schools as a concrete contribution to the development of adaptive and contextual Islamic education.